Modeling the economic impacts of oil production in sudan: An empirical analysis for productive sectors - Hassan, K. (American Scientific Publishers, 2015)
This study examines the impact of oil production and the GDP of Sudan for the period 1995 to 2012. Specifically, these impacts are in the form of, investment on Agro GDP sector. To meet this objective, secondary data were collected and analyzed using time series methods of unit root, cointegration, and multi regression. The results reveal a weak causality relationship between independent variables (public investment, foreign investment, private investment) and dependent variables namely agriculture GDP. Investment is estimated to have contributed to 58 percent of variation in agriculture GDP during post oil production period. The results of the analysis suggest that only public investment affects the agriculture GDP significantly. The forging direct investment and private investment are insignificant. Â© 2015 American Scientific Publishers. All rights reserved.